Pyruvate metabolism controls chromatin remodeling during CD4+ T cell activation - Enric Mocholi; Laura Russo; Keshav Gopal; Andrew G. Ramstead; Sophia M. Hochrein; Harmjan R. Vos; Geert Geeven; Adeolu O. Adegoke; Anna Hoekstra; Robert M. van Es; Jose Ramos Pittol; Sebastian Vastert; et al. (Cell Reports, 2023)
Summary: Upon antigen-specific T cell receptor (TCR) engagement, human CD4+ T cells proliferate and differentiate, a process associated with rapid transcriptional changes and metabolic reprogramming. Here, we show that the generation of extramitochondrial pyruvate is an important step for acetyl-CoA production and subsequent H3K27ac-mediated remodeling of histone acetylation. Histone modification, transcriptomic, and carbon tracing analyses of pyruvate dehydrogenase (PDH)-deficient T cells show PDH-dependent acetyl-CoA generation as a rate-limiting step during T activation. Furthermore, T cell activation results in the nuclear translocation of PDH and its association with both the p300 acetyltransferase and histone H3K27ac. These data support the tight integration of metabolic and histone-modifying enzymes, allowing metabolic reprogramming to fuel CD4+ T cell activation. Targeting this pathway may provide a therapeutic approach to specifically regulate antigen-driven T cell activation.